THE USE OF WORD SEARCH PUZZLES TO TEACH STUDENTSâ€™ VOCABULARY MASTERY - Chesy, Laura; Susilawati, Endang; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purposes of this research are to investigate the significant difference between the pre-test and post-test of the vocabulary mastery andÂ to find out the effect size after being taught by using Word Search Puzzles of tenth grade students of SMK PGRI Pontianak. The form of this research is a pre-experimental study with one group pre-test and post-test design. The sample of this research is class X TSM of SMK PGRI Pontianak that consists of 31 students. The technique of data collection is measurement technique and tool of data collection is a test in form of essay test. The research findings showed that the mean score of pre-test is 59.74 while the mean score of post-test is 73.09. It shows that Word Search Puzzles had improved studentsâ€™ vocabulary mastery. The result of t-test is 6.53. It is higher than t-critical value (6.53 > 2.042) in level of 0.05. As the result, the alternative hypothesis (Ha) is accepted. The calculation of effect size of the treatment is 1.17. It is higher than 0.8 and categorized as â€œHighâ€ based onÂ the t-table. It could be concluded that Word Search Puzzles is highly effective to teach vocabulary mastery to the tenth grade students of SMK PGRI Pontianak.Keywords: Word Search Puzzles, Teaching Vocabulary